Pemeriksaan Golongan Darah Di Panti Sosial Asuhan Anak Balita Tunas Bangsa Cipayung Jakarta Timur - Donny Mahendra; Yanti Anggraini; Erita Sitorus (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2023)
Blood group examination is a very important part of knowing the type of blood type as an identity. The purpose of carrying out community service is to find out the blood type of children and toddlers at the Panti Sosial Asuhan Anak dan Bangsa, Cipayung, Jakarta Timur. The number of children whose blood group examination was carried out was 89 children. The blood group examination process is divided into three sessions, the first session is for toddlers, followed by infants and the last examination is for school children. The blood group examination results varied with classifications A, B, AB and O, it was found that most of the children had blood type O as many as 33 children (37.1%). All children have positive rhesus (RH+) on blood group examination. In conclusion, the blood group examination carried out on children apart from providing the identity of the child in the orphanage is also a procedure or initial screening requirement to find out the child's blood type if something unexpected happens.